Perancangan Lingkungan Fisik Dengan Pendekatan Green Building - Y Yuliyanti (Jurnal Teknik Industri, 2016)
PG Tjoekir is a sugar manufactured by PTPN X BUMN, sugar production trough 6 phase where  each has many problem about physic environment ( health and comfort). Each room has environment with noisy level a 85 dBA, exposure level a 200 lux and temperature level a 36°C. So these problem has need design repair for environment physic with Green Building methods. This methods can be reduce noisy level, exposure level and temperature level. For  arelaize health abd comfort workroom to emloyees. The result of reserch has obtainable a design 4 exhaust fan, 4 exhaust, 3 turbin ventilation, 4 LED lamp and 3 Regupol vibration metal. About the design realize can reduce of temperature room 0,73 m/s and 44 dBA for noisy level.